Uber China - Tybout, Alice M. (London : Kellogg School of Management, 2017)
Uber China is a strategy pricing case that examines the role of customer acquisition tactics and brand positioning in entering the tantalizingly large Chinese market. The case adopts the perspective of an outside observer looking at Uber's efforts to compete in China from its entry in 2013 to its exit through its acquisition by Didi Chuxing, the highly dominant industry leader in China's ride-sharing market. After laying out the market opportunity, consumer and competitive landscape, and the various acquisition-related moves of Uber and the other major players, the case asks students to conduct a postmortem on Uber's failure in China. Specifically, they must consider what drew Uber to the opportunity in China and what it might have done differently in terms of positioning and customer acquisition to compete more effectively. First and foremost a pricingrelated discussion, the case illustrates the relationship between pricing and acquisition tactics and brand positioning and the use of both in market entry and penetration.
Originally Published InTybout, A. M. (2017). Uber China. 5-317-500. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Uber (Firm) -- Case studies; Didi Chuxing -- Case studies; Ridesharing -- China -- Case studies; Customer relations -- Management -- Case studies; Branding (Marketing) -- Case studies